Ecology and Conservation of an Endangered Tree Species Aporosa bourdillonii Stapf. from Kerala - Rakesh, R. R.; Somen, C. K.; Roby, T. J.; Mathew, J. (Indian Forester, 2018)
Aporosa bourdillonii is a little known rare, endemic tree species from the evergreen forests of Western Ghats. In Kerala, it perseveres only in an isolated location of Thrissur Forests. This study assessed the ecology, status analysis and vegetative propagation potentials of this naturally vulnerable plant. The low reproductive success of A. bourdillonii leads to the extinction of the species in the nearby future. Successful population reinforcement had been made by nursery techniques to conserve this species. The data presented in this paper would provide useful information for the conservation of this rare and endemic taxon.